Correlative microscopy of morphology and luminescence of Cu porphyrin aggregates. (18th June 2018) - Bahrami, M; Kraft, S; Becker, J; Hartmann, H; Vogler, B; Wardelmann, K; Behle, H; Elemans, J A A W; Barke, I; Speller, S
Abstract: The transfer of energy and information through molecular aggregates requires as one important building block: anisotropic, cable-like structures. Knowledge on the spatial correlation of luminescence and morphology represents a prerequisite in the understanding of internal processes and will be important for architecting suitable landscapes. In this context we study the morphology, fluorescence and phosphorescence of nanoaggregates on surfaces in a spatially correlative way. We consider lengthy strands and isotropic islands as two morphologies. It turns out that phosphorescence is quite strong compared to fluorescence and the spatial variation of the observed intensities is largely in line with the amount of dye. However, in proportion, the strands exhibit more fluorescence than the isotropic islands, suggesting weaker non-radiative channels. The ratio of fluorescence to phosphorescence appears to be correlated with the degree of aggregation or internal order. The height at which luminescence apparently saturates is explained in the context of the multireflection of incident and emitted light inside the dye. This is supported by correlative photoemission electron microscopy which is more sensitive to the surface region. The lengthy structures exhibit a pronounced polarization dependence of the luminescence with a relative dichroism of up to about 60%, revealing the substantial perpendicular orientation preference of the molecules with respect to the substrate and parallel with respect to the strands.